2018
DOI: 10.1007/s00262-018-2184-2
|View full text |Cite
|
Sign up to set email alerts
|

Absence of host NF-κB p50 induces murine glioblastoma tumor regression, increases survival, and decreases T-cell induction of tumor-associated macrophage M2 polarization

Abstract: High-grade gliomas harbor abundant myeloid cells that suppress anti-tumor immunity and support tumor growth. Targeting transcription factors, such as NF-κB p50, that mediate suppressive myeloid M2 polarization may prove therapeutic. GL261-Luc glioblastoma cells were inoculated into wild-type and p50 mice, followed by analysis of tumor growth, survival, tumor myeloid cells, and T cells. The absence of host p50 slows tumor growth and enables regression in 30% of recipients, leading to prolonged survival. Tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 39 publications
(40 reference statements)
2
25
0
Order By: Relevance
“…[33][34][35][36][37] Deletion of p50 in IMC likely impacts these factors and contributes to activation of resulting macrophages and DCs. [9][10][11][12][13][14][15][16] Consistent with this idea, we find that p50-IMC generate tumor and lymph node macrophages that co-express Ly6C and MHCII, a combination indicative of activated, tumor suppressive macrophages. 28 38-40 We previously found increased Ly6C + MHCII + tumor macrophages in glioblastomas developing in the central nervous system of p50 -/compared with WT hosts, associated with reduced glioblastoma tumor growth.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…[33][34][35][36][37] Deletion of p50 in IMC likely impacts these factors and contributes to activation of resulting macrophages and DCs. [9][10][11][12][13][14][15][16] Consistent with this idea, we find that p50-IMC generate tumor and lymph node macrophages that co-express Ly6C and MHCII, a combination indicative of activated, tumor suppressive macrophages. 28 38-40 We previously found increased Ly6C + MHCII + tumor macrophages in glioblastomas developing in the central nervous system of p50 -/compared with WT hosts, associated with reduced glioblastoma tumor growth.…”
Section: Discussionsupporting
confidence: 82%
“…28 38-40 We previously found increased Ly6C + MHCII + tumor macrophages in glioblastomas developing in the central nervous system of p50 -/compared with WT hosts, associated with reduced glioblastoma tumor growth. 16 We also find that p50-IMC generate tumor and lymph node CD11b + F4/80 -CD11c + MHCII + cDCs, which are likely also activated due to de-repression of pro-inflammatory NF-κB target genes. Of note, p50-IMC did not activate endogenous tumor myeloid cells.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…It was shown that an inhibition of transcription factors such as NF-kB, a mediator of M2 macrophages polarization, led to slower tumor growth and prolonged survival in a mouse model. It also decreased T cell induction which made the tumor less immunosuppressive (Barberi et al, 2018). Targeting NF-kB may improve the effectiveness of the current standard therapies.…”
Section: Immune Environmentmentioning
confidence: 99%
“…It is well documented Open access that myeloid cell intrinsic NF-κB signaling promotes tumor initiation and progression. [7][8][9][10][11][12] NF-κB may directly and indirectly regulate T-cell activation, tumor infiltration and function. 7-10 13-16 However, polymorphisms in NFKB1 that diminish its expression have been linked to increased risk of colorectal cancer in humans.…”
Section: Introductionmentioning
confidence: 99%